Tetrandrine Prevents Neomycin-Induced Ototoxicity by Promoting Steroid Biosynthesis - Zhang, Qilei; Wu, Yunhao; Yu, Yan; Niu, Yuguang; Fang, Qiaojun; Chen, Xin; Qi, Jieyu; Zhang, Chen; Wu, Geping; Su, Kaiming; Chai, Renjie (Frontiers in Bioengineering and Biotechnology, 2022)
Aminoglycoside antibiotics are widely used for the treatment of serious acute infections, life-threatening sepsis, and tuberculosis, but all aminoglycosides cause side effects, especially irreversible ototoxicity. The mechanisms underlying the ototoxicity of aminoglycosides need further investigation, and there are no effective drugs in the clinic. Here we showed that tetrandrine (TET), a bioactive bisbenzylisoquinoline alkaloid derived from Stephania tetrandra, ameliorated neomycin-induced cochlear hair cell injury. In both in vitro and in vivo experiments we found that TET administration significantly improved auditory function and reduced hair cell damage after neomycin exposure. In addition, we observed that TET could significantly decrease oxidative stress and apoptosis in hair cells after neomycin exposure. Finally, RNA-seq analysis suggested that TET protected against neomycin-induced ototoxicity mainly by promoting steroid biosynthesis. Collectively, our results provide pharmacological evidence showing that TET may be a promising agent in preventing aminoglycosides-induced ototoxicity.